2023
DOI: 10.1002/jrsm.1632
|View full text |Cite
|
Sign up to set email alerts
|

A critical reflection on computing the sampling variance of the partial correlation coefficient

Abstract: The partial correlation coefficient quantifies the relationship between two variables while taking into account the effect of one or multiple control variables. Researchers often want to synthesize partial correlation coefficients in a meta-analysis since these can be readily computed based on the reported results of a linear regression analysis. The default inverse variance weights in standard meta-analysis models require researchers to compute not only the partial correlation coefficients of each study but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…S22 conserves the t ‐values and the p ‐values of the original reported research; S12 does not. Equation () of van Aert and Goos 4 correctly shows how S2 reproduces the same test statistics ( t ‐values and p ‐values) as the original research studies reported and used to calculate these PCCs. In contrast, PCCs with S1 misclassify the statistical significance of reported results.…”
Section: Design Bias Rmse Coverage ρ N S12 S22 S12 S22 S12 S22mentioning
confidence: 72%
See 4 more Smart Citations
“…S22 conserves the t ‐values and the p ‐values of the original reported research; S12 does not. Equation () of van Aert and Goos 4 correctly shows how S2 reproduces the same test statistics ( t ‐values and p ‐values) as the original research studies reported and used to calculate these PCCs. In contrast, PCCs with S1 misclassify the statistical significance of reported results.…”
Section: Design Bias Rmse Coverage ρ N S12 S22 S12 S22 S12 S22mentioning
confidence: 72%
“…Partial correlation coefficients, rp, are often used as the effect sizes in the meta‐analysis and systematic review of the findings from multiple regression analysis 1–3 . Van Aert and Goos 4 reminds meta‐analysts that the variance of the partial correlation coefficient's (PCC) sampling distribution is: 5,6 S12=1rp22italicdf, where, df = the degrees of freedom available to the multiple regression used to estimate rp. Van Aert and Goos 4 claim that: “Using a suboptimal estimator of the sampling variance biases the results of meta‐analysis” (p. 4).…”
Section: Design Bias Rmse Coverage ρ N S12 S22 S12 S22 S12 S22mentioning
confidence: 99%
See 3 more Smart Citations